2015
DOI: 10.21608/jppp.2015.74710
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Population Densities of Certain Insect Pests Attacking Grapevine Trees and Their Associated Predators at Mansoura District

Abstract: The present investigation was carried out in the farm of Agriculture Research Center , Faculty of Agriculture, Mansoura University to study the effect of some weather factors on the population density of per certain insect pests infesting grapevine trees and their associated predators during the successive seasons of 2014 and 2015 at Mansoura district. The obtained results revealed that four peaks for Retithrips syriacus Manget season were recorded during the period of study. The highest number for this insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The partial regression between C. undecimpunctata population and mean temperature or the relative humidity were (b 1 = 7660 , 0.4330 and b 2 = 0.1207, 0.0925) in the two seasons, respectively. These results partially agree with those of Ghanim et al (2015) and Amer (2016) who found that temperature positively affected the population of C. undecimpunctata.…”
Section: Eleven-spotted Lady Beetle C Undecimpunctata (L)supporting
confidence: 92%
“…The partial regression between C. undecimpunctata population and mean temperature or the relative humidity were (b 1 = 7660 , 0.4330 and b 2 = 0.1207, 0.0925) in the two seasons, respectively. These results partially agree with those of Ghanim et al (2015) and Amer (2016) who found that temperature positively affected the population of C. undecimpunctata.…”
Section: Eleven-spotted Lady Beetle C Undecimpunctata (L)supporting
confidence: 92%
“…On the other hand, field studies conducted in various agricultural habitats in several governorates of the Nile Delta showed that seasonal dynamics of population density of aphids (which is the main prey of C. propinqua ), as can be expected, strongly depends on the crop. In particular, on sugar beet, a high aphid population density was observed from October to April (Hegab et al., 2018; Khalifa, 2017), on wheat, in March–May (Helmi & Rashwan, 2013), whereas on grapevine, high population densities of insect pests and their predators (including the object of our study) were recorded in May–September (Ghanim et al., 2015). Thus, it seems that C. propinqua can find a prey throughout the year, although low winter temperatures undoubtedly increase mortality and slow down larval development (Yarpuzlu & Uygun, 2010).…”
Section: Introductionmentioning
confidence: 70%
“…This polyphagous predator feeds mostly on various aphids, although feeding on soft scales, mealybugs, whiteflies and psyllids was also recorded. It often reaches high population densities and is therefore considered as an important natural enemy of insect pests (Abdel‐Salam et al., 2018; Adly et al., 2016; Atuncha et al., 2013; Badary, 2010; Bayoumy & Michaud, 2015; Catling, 1970; Dicko, 2000; Ghanim et al., 2015; Mahmoud et al., 2016; Sæthre et al., 2011; Youssif, 2019). Thus, large geographic range, wide habitat specificity and broad range of prey (including a number of pests of protected crops) suggest that C. propinqua can be considered as potential agent for biological control in greenhouses, but, as far as we know, this potential has not yet been realized.…”
Section: Introductionmentioning
confidence: 99%
“…Cheilomenes propinqua is known as an active predator of aphids, soft scales, whiteflies, mealybugs, and other small sucking pests. This predatory ladybird shows not only a wide prey range, but also broad habitat specificity reaching high population densities in fields, orchards, vineyards, and other agricultural landscapes [44][45][46][47][48][49][50][51][52][53][54]. Preliminary laboratory studies showed that C. propinqua has a number of desirable properties of a potential successful mass-reared biocontrol agent: rapid pre-adult development (10-11 days), high voracity (depending on prey species, larva consumed a total of about 500 aphids, female consumed 40-80 aphids per day), high lifetime fecundity (about 1000 eggs per female) and prey search activity [20,[55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%